2023
DOI: 10.1038/s41467-023-37489-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly and population genomic resource to accelerate orphan crop lablab breeding

Abstract: Under-utilised orphan crops hold the key to diversified and climate-resilient food systems. Here, we report on orphan crop genomics using the case of Lablab purpureus (L.) Sweet (lablab) - a legume native to Africa and cultivated throughout the tropics for food and forage. Our Africa-led plant genome collaboration produces a high-quality chromosome-scale assembly of the lablab genome. Our assembly highlights the genome organisation of the trypsin inhibitor genes - an important anti-nutritional factor in lablab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 107 publications
5
21
2
Order By: Relevance
“…uncinatus, uncharacteristically clustered with 4-seeded accessions which is not in line with what has been reported previously [19,72] and hence needs further investigation further. However, phylogenetic analysis based on agro-morphological data clustered all 2-seeded accessions into cluster I (Fig 1) with only two 4-seeded accessions (24783 and 21048) included as predicted previously by Njaci et al [19]. Interestingly 24783, is a 4-seeded lablab accession which clustered with the 2-seeded accessions in both SNP and morphological data based phylogenetic trees (Fig 1) while 21048 was not successfully genotyped.…”
Section: Genetic Diversity Among Lablab Accessionscontrasting
confidence: 73%
See 3 more Smart Citations
“…uncinatus, uncharacteristically clustered with 4-seeded accessions which is not in line with what has been reported previously [19,72] and hence needs further investigation further. However, phylogenetic analysis based on agro-morphological data clustered all 2-seeded accessions into cluster I (Fig 1) with only two 4-seeded accessions (24783 and 21048) included as predicted previously by Njaci et al [19]. Interestingly 24783, is a 4-seeded lablab accession which clustered with the 2-seeded accessions in both SNP and morphological data based phylogenetic trees (Fig 1) while 21048 was not successfully genotyped.…”
Section: Genetic Diversity Among Lablab Accessionscontrasting
confidence: 73%
“…In this study, two QTL, on chromosomes Lp1 and Lp9, were significantly associated with NoDF (Fig 4). However, Njaci et al [19] reported QTL on a different chromosome for the same trait suggesting that different regions of the genome may be impacting on this trait.…”
Section: Novel Genomic Resources To Identify Candidate Loci In Lablabmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to achieve high-quality chromosome-level de-novo assembly, the most commonly-used approach integrates low-error second-generation sequencing (SGS), long-read TGS, and Hi-C sequencing 26,27,28,29 . Firstly, long TGS reads are assembled into contigs.…”
mentioning
confidence: 99%